Menghadapi Narasi Pembangunan: Dilema dan Ambiguitas Program Bantuan Asing di Afrika Sub-Sahara - Yosan Efendi (Terekam Jejak Publisher, 2023)
Foreign aid programs have been a major focus for many Sub-Saharan African countries in the process of development. In recent years, foreign aid programs have significantly contributed to the economy and social development in Africa. However, in their implementation, foreign aid programs face several dilemmas and ambiguities, which sometimes result in unintended consequences for the recipient communities. This study aims to examine the dilemmas and ambiguities of foreign aid programs in Sub-Saharan Africa, with a focus on their social, economic, and political impacts. The results of this research indicate that while foreign aid programs can help Sub-Saharan African countries achieve development goals, such as reducing poverty and improving health and education, their implementation often creates problems and dilemmas that affect their outcomes. Some of the dilemmas faced are the dependency on foreign donors, lack of community participation, lack of coordination between recipient countries and donors, and lack of accountability from the recipient government. Therefore, it is recommended that in their implementation, foreign aid programs should consider community involvement and proper coordination between recipient countries and donors.